QUALITY CONTROL OF HEALTH SERVICES WITH PATIENT SATISFACTION IN PUSKESMAS BAITURRAHMAN BANDA ACEH - Andika, Fauziah; Hariyanto, Prima (Universitas Ubudiyah Indonesia, 2017)
Quality of health services is strongly influenced by the quality of physical advice, types of personnel available, medicines, medical devices and other supporting facilities, service delivery process, and compensation received and expectations of the user community. The purpose of this study was to determine the relationship of nurse service quality with patient satisfaction in Baiturrahman Puskesmas, this research is quantitative using analytic with cross sectional design. The population in this study were all the people who visited the puskesmas baiturrahman, which amounted to 85,775 and used the slovin formula in obtaining a sample of 99 people. This data collection was taken on March 06, 2017. Data analysis using computer application, based on univariate analysis, the result of satisfaction satisfied 46 patients (46,5%) less satisfied 53 (53,5%), good knowledge 40 (40,4%) 59 (59,6%), access to service available 33 (33,3%) not available 66 (66,7%), complete health facility 42 (42,4%) less complete 57 (57,6%) , comfortable comfort 34 (34,3%) less comfortable 65 (65,7%) and Bivariat Analysis got result that relation of health service access with patient satisfaction with 0.008 <Î± = 0.05, patient satisfaction relationship with service facility with 0,042 <Î± = 0.05, patient satisfaction relationship with comfort with 0.016 <Î± = 0.05, patient satisfaction relationship with knowledge with 0.015 <Î± = 0.05, or there is a relationship between patient satisfaction with access to services, there is a relationship between patient satisfaction with service facilities, patient satisfaction with officer reliability, exist the relationship between patient satisfaction with comfort, there is anatara patient satisfaction with knowledge with.Keywords : Patient satisfaction, quality of service